2015
DOI: 10.1126/science.aab1879
|View full text |Cite
|
Sign up to set email alerts
|

Layered deformation in the Taiwan orogen

Abstract: The underthrusting of continental crust during mountain building is an issue of debate for orogens at convergent continental margins. We report three-dimensional seismic anisotropic tomography of Taiwan that shows a nearly 90° rotation of anisotropic fabrics across a 10- to 20-kilometer depth, consistent with the presence of two layers of deformation. The upper crust is dominated by collision-related compressional deformation, whereas the lower crust of Taiwan, mostly the crust of the subducted Eurasian plate,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
71
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 33 publications
(100 reference statements)
6
71
2
Order By: Relevance
“…More complex anisotropy structure follows from the analysis of the group and phase velocities of surface waves derived from ambient noise correlation in a recent study by Huang et al . []. These authors found clear SN oriented anisotropy in the upper crust and almost perpendicular orientations below 10 km depth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More complex anisotropy structure follows from the analysis of the group and phase velocities of surface waves derived from ambient noise correlation in a recent study by Huang et al . []. These authors found clear SN oriented anisotropy in the upper crust and almost perpendicular orientations below 10 km depth.…”
Section: Introductionmentioning
confidence: 99%
“…This seems to be consistent with the results of Huang et al . [], who found a switch in the anisotropy patterns from coast parallel in the crust to coast perpendicular in the uppermost mantle. These and other studies show that the anisotropy structure beneath Taiwan is fairly complicated, and the inconsistencies between different models appear to be quite important.…”
Section: Introductionmentioning
confidence: 99%
“…This uncertainty is largely due to the difficulty of making direct observations of deformation in the deep crust to test the predictions made by conceptual models. On page 720 of this issue, Huang et al ( 1) use observations of seismic anisotropy to constrain the geometry of deformation in the continental crust beneath the Taiwan orogen, and thus shed light on how the crust deforms as mountains are formed.…”
mentioning
confidence: 98%
“…Another important question is to what extent the mantle lithosphere, in addition to the lower crust, participates in deformation. More generally, the observation and interpretation of crustal anisotropy, both in mountain belts and in other tectonic settings, represents an exciting frontier area, enabled by the increasing availability of data from dense seismic networks and the maturation of observational techniques that rely on the ambient noise field ( 1,8) or on the analysis of converted waves ( 9). Furthermore, new constraints on the relationships between strain and anisotropy in crustal rocks ( 10,11) are enhancing our ability to relate seismic observations to deformation geometry, opening the door to the detailed and quantitative testing of hypotheses related to the deformation of Earth's crust.…”
mentioning
confidence: 99%
“…About a decade ago, theoretical derivations demonstrated that the cross-correlation of continuous ambient noise between two stations predominantly yields fundamental-mode Surface wave Green's functions (e.g., Lobkis and Weaver 2001;Lobkis 2001, 2004;Derode et al 2003;Snieder 2004;Wapenaar 2004;Larose et al 2005;Snieder and Wapenaar 2010). As a result, the ambient noise tomography method has been widely used to investigate crust and mantle velocity structures (e.g., Lin et al 2007;Huang et al 2012Huang et al , 2015. In comparison with the conventional approach using earthquake sources (e.g., Yeh et al 2016), the merits of this application include that it is free from earthquake source distribution limitations and the resolution depends solely on the station distribution.…”
Section: Introductionmentioning
confidence: 99%